(untitled) - Peter William Atkins (Oxford, New York, 1994)
The book provides detailed solutions to all end-of-chapter Exercises and problems of physical chemistry. Most of the solutions have a few more words of explanation and often an additional step or two. Comments and questions have often been appended to the solution to help clarify the significance of the Exercise or Problem, or its result, and to edicate small extensions. When the results of untermediate calculations are shown, they are often given with one more figure than would be justified by the data
Keywords: chemistry, physical and theoretical